Overview of the PMBOK® guide short cuts for PMP® certification - Ó Conchúir, Deasún (Springer Berlin Heidelberg, 2011)
This book is for everyone who wants a readable introduction to best practice Project Management, as described by the "PMBOK[registered] Guide, 4th Edition" of the Project Management Institute (PMI), 'the world's leading association for the project management profession'. It is particularly useful for applicants for the PMI's PMP[registered] (Project Management Professional) and CAPM[registered] (Certified Associate of Project Management) examinations, which are based mostly on the "PMBOK[registered] Guide". This book can also be studied alone by anyone as a general introduction.